O CUIDADO TERRITORIAL EM SAÚDE E AS POPULAÇÕES ORIGINÁRIAS: NARRATIVAS NA COOPERAÇÃO INTERNACIONAL DO PROGRAMA MAIS MÉDICOS - MARCUS VINÍCIUS MARCELINI SILVEIRA RIBEIRO (2023)
This project proposes to identify the effects of professional health care, based on the experience of academic supervision of the More Doctors for Brazil Program (PMMB) with Cuban cooperative doctors in primary health care for native peoples, in the indigenous health system of Amazon region. The project develops from theoretical connections with the narratives of the experience and routine as an academic supervisor, as well as the documentary analysis of articles, books and public documents, all of which are freely accessible. The aim is to identify themes arising from professional practice in order to deepen and produce theoretical connections with the empirical field, based on permanent education and the development of professional practice. The reflections go through the theme of access to health, clinical situations, intercultural dialogues, academic supervision and work logistics in this region. As results, an article was developed that seeks to relate the Mais Médicos Program, the researcher's narratives about his professional practice and the possibilities of health education in such a context. Also, an article on the confrontation of the Covid-19 pandemic in Amazonas by the health teams and the narratives about the researcher's experiences with health education activities, in the indigenous health of the Mais Médicos Program, in that period. Finally, an article on narrative research as a counter-hegemonic method of research and data organization, as well as a field capable of opening up possibilities for authentic scientific productions that understand that research also serves as an instrument of denunciation and social transformation.